Applied design of the home - Gaden, Mary (My University, 1908)
Introduction: The question of arrangement and design is not an insignificant problem that has only significance with the wealthy “few,” but it is a question that all are concerned about in our dwellings, belongings, and even their own person.
Citation: Gaden, Mary. Applied design of the home. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Domestic Science; Home Economics; Design; Handwritten; Graduating theses; Senior theses; Theses